PENGEMBANGAN SENSOR JARAK BERBASIS FLUXGATE - Zannuraini, Zannuraini; Djamal, Mitra; Indrasari, Widyaningrum (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
A fluxgate is a magnetic sensor which works by comparing the measured magnetic field with the magnetic field reference, this sensor has been developed in various fields. This research aims to develop one of fluxgate aplication that is proximity sensor. Methode in this research is experiment with the steps are the manufacture of sensors, characterization and calibration sensor to distance. The result is fluxgate sensor with the ovale core Vitrovac type 6025Z, it has excitation coil about 360 windings and pick up coil about 240 windings. The characterization of sensor is known that the sensor has a sensitivity of 1639,7 mV/ Î¼T and work in the area Â± 2,3 Î¼T, with the maximum absolute error is 0,15298 Î¼T and maximum relative error is 3,257 %. From the calibration of distance has obtained that the sensor works at a distance from. 15,86 â€“ 27 mm. Keywords: Fluxgate, proximity sensor.